Pre-service teachers' visual images about biology - Esra Kızılay; Mustafa Hamalosmanoğlu (International Journal of Evaluation and Research in Education (IJERE), 2019)
The aim of this study was to investigate the visual images of pre-service teachers who take biology courses in undergraduate education about biology by analyzing their drawings. The research was conducted with 97 pre-service teachers, studying at the education faculty of a university in Turkey and taking biology course during undergraduate training. Science teaching and classroom teaching departments were included in the research. In the study, the data collection tool has been applied based on voluntariness of pre-service teachers. In the first part of the data collection, information about pre-service teachers' department, grade level and gender were collected. In the second part, pre-service teachers were given a blankA4 paper and asked to draw a picture explaining the concept of biology. Pre-service teachers completed their drawings in approximately 20 minutes. Content analysis was used in the analysis of the drawings. Categories and codes were first determined in the analysis of the data. Drawings were coded separately by two researchers. Then, in order to ensure inter-coder reliability, the codes were evaluated together, and a decision was reached. The analysis of pre-service teachers' drawings about biology shows that ecology and ecosystem concepts came to the mind of the majority when biology is mentioned. The general result of the research can be stated as the visual images of pre-service teachers about biology are mostly shaped within the framework of ecology.